Clinical assessment of patients with cervicogenic headache: a preliminary study - Hong, Jia-Pei; Lai, Cheng-Hsiu; Lin, Yin-Chou; Chou, Shih-Wei (Chang Gung medical journal, 2010)
The traditional diagnostic criteria of cervicogenic headache (CEH) are mainly subjective symptoms, thus making its differential diagnosis difficult. This study aimed to evaluate the diagnostic validity of functional plain radiograms, based on the clinical diagnostic criteria of CEH. Twenty-two patients with subjectively diagnosed cervicogenic headache, including 7 with a traceable history of neck trauma, and 14 healthy subjects as controls from rehabilitation clinics were evaluated. All of them received plain cervical radiographic examination, including lateral views in the flexion, neutral, and extension positions. The degree of localized kinking was measured to define the level of cervical malalignment. Subjective symptoms elicited by a questionnaire were categorized by involved regions. The numbers of localized kinking segments in the lower cervical spine were significantly different between the study and control groups (p < 0.05). The study group had more involved segments than the control group. On the questionnaire, clinical symptoms involving the nasal regions were one of the most common clinical manifestations (36.4%) among cephalic syndrome. For cervicogenic headache, functional plain radiogram may help in clinical diagnosis. Abnormal nociceptive afferents due to malalignment may be responsible for the nasal symptoms.